(untitled) (Journal of the College of Basic Education, 2022)
The ethnographic composition is more important in determining the political weight of the state, and it means the peoples, nationalities, races, religions, and languages ​​that exist within the framework of political unity (), as it is the most important factor influencing the cohesion of states, their unity, and then their stability. , and harmony enjoys stability, and this in turn is reflected in its strength and political status, while the existence of ethnic diversity leads to instability of the state, which leads to weakening cohesion and fusion among the members of society, as it impedes administration and governance, and weakens the political power of the state, especially if it is That state has enemies lurking around, taking advantage of this discrepancy, and then working to tear its unity ().